THE QUALITY OF PUBLIC SERVICES AND THEIR IMPACT ON COMMUNITY SATISFACTION IN BONGOMEME VILLAGE, DUNGALIYO SUB-DISTRICT GORONTALO COUNTY - Danial, Titin A; Igirisa, Irawaty; Tantu, Romy (Universitas Negeri Gorontalo, 2024)
This study aims to determine the quality of public services and their effect on community satisfaction in Bongomeme Village, Dungaliyo District, Gorontalo Regency. The approach in this study is quantitative with ex-post facto methods. Data collection in this study was carried out by questionnaire. The number of samples was 62 people consisting of 12 village officials and 50 community members. Data analysis in this study is a simple linear regression inferential quantitative analysis. The results showed that the quality of public services was in a fairly good category with a score of 78.16%. This means that public services in Bongomeme Village, Dungaliyo District, Gorontalo Regency have not been able to achieve the desired goals or do not fully meet the needs of the community with satisfactory results or in this case the services provided have not provided significant benefits to the local community. Then the quality of public services has a positive and significant effect on community satisfaction in Bongomeme Village, Dungaliyo District, Gorontalo Regency with a coefficient of determination of 72.60%. The influence of other variables on community satisfaction amounted to 27.40%, namely village government motivation in the form of assistance and ease of service affairs, speed of service, social relations and community psychological factors. Positive results show that community satisfaction in Bongomeme Village, Dungaliyo District, Gorontalo Regency for the public services provided can be maximized through efforts to strengthen service quality in accordance with the expectations of the community as users of these services.